Thermally Stable Piezoelectric Performance of MnO2 Inserted Pseudo-tetragonal Phase Existent CaBi2Nb2O9-based Ceramics. (10th November 2022) - Jabeen, Nawishta; Hussain, Ahmad; Nawaz, Sajid; Qaiser, Muhammad Adnan; Zafar, Rizwan; Ishtiaq, Sadaf; Ahmed, Fahim; Masud, Usman; Sultan, Taimur; Muntaha, Sidra Tul
ABSTRACT: Pseudo-tetragonal phase boundary existent Ca0.60 (Li0.5 Bi0.5 )0.40 Bi2 Nb2 O9 : x wt%MnO2 (CBNL: x Mn) ceramic series is fabricated to investigate the ferroelectric and piezoelectric properties. Pure CBNL and CBNL: x Mn ceramics have maintained their pseudo-tetragonal phase boundary even after the insertion of Mn ions. The addition of MnO2 in CBNL has improved the multifunctional properties of material at x = 0.20. CBNL:0.20Mn has shown the relative density of 98%, saturated polarisation ( PS ) of ~ 13.5 µC/cm 2, high piezoelectric coefficient ( d33 ) of ~ 25 pC/N, and high impedance of ~ 8.9 × 10 8 Ω at room temperature, which are the much improved values as compared to pure CBN or CBNL ceramics. The dielectric constant ( ɛr ) dependence on temperature is presenting the sharp peak of CBNL:0.20Mn ceramic at Curie temperature ( TC ) ~ 918°C confirming the strong ferroelectric nature of the ceramic. Importantly, poled CBNL:0.20Mn ceramic has shown the thermally stable depoling performance, which remains 92% (23 pC/N) of its initial room temperature value even after annealing the sample at 800°C. Results indicate the clear significance that the introduction of multivalence Mn ions in the pseudo-tetragonal existent region of CBNL has improved the multifunctional properties of the material, making it a strong candidate to be utilised in actuators and high-temperature piezoelectric devices.